Fresno County Bar Association Bar Banquet at TorNino's - Watkins, Howard::::::::: (1984)
Rosie and The Supremes doing finale song with leg kicks; Mary Louise Frampton as Rosie; Val Saldana, Jim Lambe, Robert Jones and Sam Vallis as The Supremes